Síntese de heterociclos nitrogenados através de reações de funcionalização C-H de azaarenos e avaliação da atividade antiparasitária - Borges, Natália Menezes Moreira (2022)
The neglected diseases caused by parasites, such as Chagas´ disease, sleeping sickness and leishmaniasis, affect thousands of people every year, mainly in tropical and underdeveloped countries. Due to the lack of efficient drugs for the treatment, these diseases lead many of the infected to death. Thus, the development of new methods for the synthesis and functionalization of compounds with potential antiparasitic activity is of great importance. Among the organic compounds which draws attention from the medicinal chemistry point of view, the nitrogen heterocycles constitute a class of privileged compounds due to their wide variety of biological activities. The quinazolines and isoquinolines, for example, are widely studied, since their structure are present in many bioactive compounds. Quinazolines, in particular, have had their antiparasitic activities studied and reported. The C-H functionalization reactions have emerged as an important tool for the functionalization of N-heterocycles. These reactions allow the increase of structural diversity without the use of previously functionalized molecules. Thus, it is possible to obtain a diverse library of compounds in a reduced number of steps, implying in the reduction of reactants and waste generation. Among the reactions named as C-H functionalization, the reactions involving C(sp3)-H bonds of azaarenes have been widely studied in recent years, once they allow direct functionalization without the use of harsh reaction conditions, given the favored reactivity of the azaarenes. This work aimed the synthesis of quinazoline and isoquinoline derivatives employing C-H functionalization of azaarenes, through conjugated addition to trans-β-nitrostyrenes. Initially, it was studied the synthesis of N-heteroarenylacrylonitriles through Michael addition of 4-methylquinazolines to -nitrostyrenes, followed by direct conversion of the nitro group into a nitrile. Using the optimized conditions, 22 examples were obtained with moderated to good yields. The reaction mechanism has also been studied, in order to gain some insights about this new method. Posteriorly, it was studied the C(sp3)-H functionalization of 4-methylquinazolines and 1-benzylisoquinolines, utilizing α-substituted -nitrostyrenes. In this step, 20 pyrrolo[1,2-c]quinazolines and 4 pyrrolo[2,1-a]isoquinolines were obtained. Finally, the antiparasitic activity of 20 synthetized compounds was evaluated against Trypanosoma cruzi, Plasmodium falciparum e Leishmania infantum. Interesting results were obtained concerning the biological activity against T. cruzi, which allows to continue the studies of compounds with potencial activity for the treatment for Chagas´ disease.